2007
DOI: 10.1016/j.cardiores.2007.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Globular and full-length forms of adiponectin mediate specific changes in glucose and fatty acid uptake and metabolism in cardiomyocytes

Abstract: These results clearly demonstrate that gAd and fAd mediate distinct and time-dependent effects on cardiomyocyte energy metabolism via AdipoR1 and AdipoR2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 39 publications
3
93
0
1
Order By: Relevance
“…5B). These data resemble those reported by Palanivel et al (2007) who found recombinant adiponectin produced with a mammalian expression system likewise preferentially formed high and medium size oligomers. By contrast, globular adiponectin predominantly formed dimers, with only small amounts of trimers and possibly tetramers visible.…”
Section: Discussionsupporting
confidence: 89%
“…5B). These data resemble those reported by Palanivel et al (2007) who found recombinant adiponectin produced with a mammalian expression system likewise preferentially formed high and medium size oligomers. By contrast, globular adiponectin predominantly formed dimers, with only small amounts of trimers and possibly tetramers visible.…”
Section: Discussionsupporting
confidence: 89%
“…After 4 h of transfection, the medium was replaced with ␣-minimum essential medium containing 10% FBS, and the cells were harvested for 48 h. Isolation of RNA, cDNA synthesis, primers, and qRT-PCR condition for AdipoR1 and AdipoR2 were conducted as described (16).…”
Section: Methodsmentioning
confidence: 99%
“…Small interfering RNA to knockdown expression of AMPKα L6 cells were cultured in 24-well tissue culture plates and transfected for 24 h with 50 nmol/l AMPKα1 (also known as PRKAA1) and 50 nmol/l AMPKα2 (also known as PRKAA2), or with scrambled small interfering RNA (siRNA) (Silencer Negative Control 1 siRNA; Ambion, Austin, TX, USA) as previously described [29]. siRNA sequences for AMPKα1 and AMPKα2 were: AMPKα1 GCAUAUGCUGCAGGUAGAU; AMPKα2, CGUCAUU GAUGAUGAGGCU (Ambion).…”
Section: Methodsmentioning
confidence: 99%